Incidence of Recurrence in Posterior Circulation Childhood Arterial Ischemic Stroke - Uohara, Michael Y. (JAMA Neurol, 2017)
IMPORTANCE: Childhood arterial ischemic stroke (CAIS) affects approximately 1.6 per 100 000 children per year, while stroke recurs in up to 20%of patients at 5 years. Factors determining the risk of recurrence are incompletely understood. OBJECTIVE: To investigate the incidence of the recurrence of CAIS in the posterior and anterior circulations to determine if the risk differs between the 2 locations. DESIGN, SETTING, AND PARTICIPANTS: A retrospective analysis of CAIS was conducted among children enrolled in a single-center prospective consecutive cohort at The Children’s Hospital of Philadelphia between January 1, 2006, and January 1, 2015. Children with confirmed CAIS occurring between 29 days and 17.99 years were evaluated for inclusion. Patients were excluded if infarcts were located in both the anterior and posterior distributions or if CAIS occurred as a complication of intracranial surgery or brain tumor. MAIN OUTCOMES AND MEASURES: Stroke recurrence. RESULTS: The study population included 107 patients (75 boys [70.1%] and 32 girls [29.9%]; median age at AIS, 7.7 years [interquartile range, 3.1–13.6 years]). Sixty-one children had anterior circulation CAIS (ACAIS) and 46 had posterior circulation CAIS (PCAIS). Median follow-up was 20.9 months (interquartile range, 8.7–40.4 months). For ACAIS, recurrence-free survival was 100% at 1 month and 96%(95%CI, 85%–99%) at 1 and 3 years. For PCAIS, recurrence-free survival was 88%(95%CI, 75%–95%) at 1 month and 81%(95% CI, 66%–90%) at 1 and 3 years. The hazard ratio for recurrence after PCAIS compared with ACAIS was 6.4 (95%CI, 1.4–29.8; P = .02) in univariable analysis and 5.3 (95%CI, 1.1–26.4; P = .04) after adjusting for sex and cervical dissection. CONCLUSIONS AND RELEVANCE: We identified a subgroup of patients that comprise more than 80% of recurrences of CAIS. Three years after incident stroke, 19% of children with PCAIS had a recurrence compared with 4%of patients with ACAIS. Different mechanisms of stroke may account for this difference. Children with PCAIS may warrant increased monitoring. This study highlights the necessity for further research focused on recurrence prevention.